Proceedings of the 4th Workshop on Argument Mining 2017
DOI: 10.18653/v1/w17-5107
|View full text |Cite
|
Sign up to set email alerts
|

Argument Relation Classification Using a Joint Inference Model

Abstract: In this paper, we address the problem of argument relation classification where argument units are from different texts. We design a joint inference method for the task by modeling argument relation classification and stance classification jointly. We show that our joint model improves the results over several strong baselines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Similarly, some tasks can inform each other, for example, whereas Feng and Hirst (2011) showed that argument scheme instances could be classified given general relations between ADUs, Lawrence and Reed (2015) showed that such general relations can be determined by classifying argument scheme components directly from segmented text. This inter-dependency between tasks has given rise to a growth in the application of multi-objective learning approaches (e.g., Eger, Daxenberger, and Gurevych 2017;Hou and Jochim 2017;Galassi, Lippi, and Torroni 2018;Morio and Fujita 2018), where all tasks are learned and performed at the same time. These examples highlight how the simple pipeline view of argument mining, which characterizes a lot of older research work, is increasingly being superceded by more sophisticated and interconnected techniques.…”
Section: Figurementioning
confidence: 99%
“…Similarly, some tasks can inform each other, for example, whereas Feng and Hirst (2011) showed that argument scheme instances could be classified given general relations between ADUs, Lawrence and Reed (2015) showed that such general relations can be determined by classifying argument scheme components directly from segmented text. This inter-dependency between tasks has given rise to a growth in the application of multi-objective learning approaches (e.g., Eger, Daxenberger, and Gurevych 2017;Hou and Jochim 2017;Galassi, Lippi, and Torroni 2018;Morio and Fujita 2018), where all tasks are learned and performed at the same time. These examples highlight how the simple pipeline view of argument mining, which characterizes a lot of older research work, is increasingly being superceded by more sophisticated and interconnected techniques.…”
Section: Figurementioning
confidence: 99%
“…Some use deep learning to find attacks in discussions (Cocarascu and Toni, 2017). Closer to this paper, others determine them in a given set of arguments, using textual entailment (Cabrio and Villata, 2012) or a combination of markov logic and stance classification (Hou and Jochim, 2017). In principle, any attacking argument denotes a counterargument.…”
Section: Related Workmentioning
confidence: 99%
“…Argument Mining. There is an increasing number of works in the computational argumentation research field in recent years, such as argument mining (Shnarch et al, 2018;Trautmann et al, 2020), argument relation detection (Rocha et al, 2018;Hou and Jochim, 2017), argument quality assessment (Wachsmuth et al, 2017;Gleize et al, 2019;, argument generation (Hua and Wang, 2018;Hua et al, 2019a;Schiller et al, 2020), etc. Stab and Gurevych (2014) and Persing and Ng (2016) both propose pipeline approaches to identify argumentative discourse structures in persuasive essays, which mainly includes two steps: extracting argument components and identifying relations.…”
Section: Related Workmentioning
confidence: 99%